The Deliberative Action in the Labor Market of Iraqi Art The Concepts and the Application: شيماء وهيب خضير (Al-Academy, 2019)
The analysis of the orientations of Iraqi art commodification contributed to the discovery of deliberation, which was founded in the deliberative discourse in the trends towards commodification in the Iraqi art, since the important transformations in social structures and relations produced a dictionary with new vocabulary and tools that replaced the traditions and norms that have been in circulation for a century. Deliberation and commodification have become more prevalent in the mechanics and trends of the art where the pace of change is becoming increasingly frantic towards the market. The general market for art constitutes one of the most effective phenomena within contemporary art, that there has been a proliferation of sales auctions, markets and halls and became part of the production process, and there is a general agreement on the deliberative consumerism and the functional use which has reverted the course of art in different directions in its procedural form. The research has adopted the descriptive analytical approach that determines the image which the phenomenon of deliberation must take. This approach is not limited to knowing the characteristics of the phenomenon, but extends beyond that to know the variables and factors that cause its existence, diagnosis and description, and the research will has adopted the applied approach in the analysis of some of its outputs.